MEMPROGRAMKAN PENGENALAN BANK SYARIAH PADA DESA DUKUH, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Trihantana, Rully; Mursyidah, Azizah; Aprilia (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2025)
This community service aims to introduce the basic concepts of sharia banking to people who still don't know about sharia banking due to limitations or other things in Dukuh Village, Cibungbulang District, using the Participatory Action Research (PAR) method which involves the community in identifying needs and evaluating them Held on 13 July–14 September 2024, activities include observations, discussions and educational outreach regarding basic sharia banking concepts. The results show an increase in public understanding of sharia banking as well as identification of local potential for sharia economic development. This activity is the first step in building an inclusive and sustainable sharia financial system in Dukuh Village